2012
DOI: 10.1371/journal.pone.0035330
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Cognitive-Behavioral Therapy for Subthreshold Depression and Presenteeism in Workplace: A Randomized Controlled Trial

Abstract: BackgroundSubthreshold depression is highly prevalent in the general population and causes great loss to society especially in the form of reduced productivity while at work (presenteeism). We developed a highly-structured manualized eight-session cognitive-behavioral program with a focus on subthreshold depression in the workplace and to be administered via telephone by trained psychotherapists (tCBT).MethodsWe conducted a parallel-group, non-blinded randomized controlled trial of tCBT in addition to the pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 41 publications
2
58
0
2
Order By: Relevance
“…Most of the studies included in the meta-analysis evaluated the effectiveness of a psychological intervention in older adults and pregnant women, respectively [50,51] . Those studies including an adult population (18-65 years) showed similar effect sizes as those found in the present trial, ranging from d = 0.69 to d = 0.80 [52,53] . The observed within-group effect size in the intervention group (d = 1.06, 95% CI: 0.86-1.27) is also comparable to the pre-to post-improvement effect size in the only published study on an Internet-based treatment for sD in adults aged 50 and older (d = 1.00) [19] .…”
Section: Discussionsupporting
confidence: 85%
“…Most of the studies included in the meta-analysis evaluated the effectiveness of a psychological intervention in older adults and pregnant women, respectively [50,51] . Those studies including an adult population (18-65 years) showed similar effect sizes as those found in the present trial, ranging from d = 0.69 to d = 0.80 [52,53] . The observed within-group effect size in the intervention group (d = 1.06, 95% CI: 0.86-1.27) is also comparable to the pre-to post-improvement effect size in the only published study on an Internet-based treatment for sD in adults aged 50 and older (d = 1.00) [19] .…”
Section: Discussionsupporting
confidence: 85%
“…The BA program used in this study was originally revised for university students, based on a CBT program for adults with subthreshold depression developed in a previous study by Furukawa et al (2012).…”
Section: Treatmentmentioning
confidence: 99%
“…68,69 Although originally developed for Englishspeaking primary care patients, the program has been adapted for different populations and translated into multiple languages. [70][71][72][73][74] Based on our prior TBI telephone counseling studies, 59,75 the intervention protocol was tailored in several ways to individuals living with TBI. Brief care management at the beginning of each session addressed issues specific to promoting TBI rehabilitation and recovery, 76 including return to work or school, substance abuse, social and interpersonal isolation, and transportation difficulties.…”
Section: Cbt-tbi Interventionmentioning
confidence: 99%